2020
DOI: 10.3390/app10030946
|View full text |Cite
|
Sign up to set email alerts
|

Spouted-Bed Gasification of Flame Retardant Textiles as a Potential Non-Conventional Biomass

Abstract: Renewable energy from thermal valorization plays a key part in today’s energy from natural cellulosic textiles that are resourceful biomass and safe from toxicity at high temperature treatments. The situation is opposite, when technical textiles are treated with synthetic chemical finishes adding functionality as anti-bacterial, water repellent or flame retardant, etc. Incineration of flame retardant textile results in possible unfavorable gases, toxic fumes and contaminated ash. Other thermal valorization tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 40 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…Gasification was suggested as an alternative to incineration of flame-retardant cotton textiles, which can release toxic gases and contaminated ash [67]. Textiles were gasified in a spouted bed gasification plant.…”
Section: Thermal Recyclingmentioning
confidence: 99%
See 1 more Smart Citation
“…Gasification was suggested as an alternative to incineration of flame-retardant cotton textiles, which can release toxic gases and contaminated ash [67]. Textiles were gasified in a spouted bed gasification plant.…”
Section: Thermal Recyclingmentioning
confidence: 99%
“…The presence of flame retardant in the textiles was found to lower the gasification temperature and syngas production. Removal of flame retardant prior to textile gasification resulted in higher volatile contents and moisture and lower carbon concentrations [67]. Vela et al performed steam gasification of cotton and polyester using a fluidized bed reactor and found cotton to be more suitable for syngas production [68].…”
Section: Thermal Recyclingmentioning
confidence: 99%
“…Storage and transport must also be done according to specific regulations. The proper disposal of waste wool is thus associated to high costs (around 150 €/ton [93]). This results in the increase in burning or burial alternatives, leading to serious environmental impacts: contrarily to other textile residues [93], wool residues cannot be burned easily.…”
Section: Wool Residues and Hydrolysismentioning
confidence: 99%
“…Giulio et al [35] investigated annular combustors, and the results showed how small differences between the flame responses lead to one strong topological change in the dynamical system phase space, making the system prefer orientation angles at two azimuthal locations, one opposite of the other in the annulus, as found in the experiments. Sohail et al [36,37] studied the spouted-bed gasification of flame-retardant textiles based on combustion chamber dynamics, and found that thermal value-added techniques (e.g., gasification) would help to avoid the formation of additional toxic hazards. Alternative solutions were provided as well.…”
Section: Introductionmentioning
confidence: 99%